2020
DOI: 10.1002/jbio.201960172
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of near infrared fiber optic spectroscopy for noninvasive bone assessment

Abstract: Approaches for noninvasive bone quality assessment are of great clinical need, particularly in individuals that require close monitoring of dis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 46 publications
(57 reference statements)
2
16
0
1
Order By: Relevance
“…41 As NIR radiation has been shown to be safe for clinical use, 42,43 a recent feasibility study from our lab explored NIR spectroscopy as a potential nondestructive, transcutaneous approach for assessment of bone in individuals with OI. 44 In that study, positive correlations were found between NIR-determined compositional parameters and bone mineral density. 44 Here, we used NIR spectroscopy, combined with traditional attenuated total reflectance Fourier transform infrared (ATR FT-IR) spectroscopy, to investigate changes in water and matrix and mineral components in the bones of OIM mice that had been treated with different regimens of antiresorptive drugs, alendronate (ALN) and RANK-Fc.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…41 As NIR radiation has been shown to be safe for clinical use, 42,43 a recent feasibility study from our lab explored NIR spectroscopy as a potential nondestructive, transcutaneous approach for assessment of bone in individuals with OI. 44 In that study, positive correlations were found between NIR-determined compositional parameters and bone mineral density. 44 Here, we used NIR spectroscopy, combined with traditional attenuated total reflectance Fourier transform infrared (ATR FT-IR) spectroscopy, to investigate changes in water and matrix and mineral components in the bones of OIM mice that had been treated with different regimens of antiresorptive drugs, alendronate (ALN) and RANK-Fc.…”
Section: Introductionmentioning
confidence: 77%
“…A recent feasibility study from our group showed the potential of NIR spectroscopy as a noninvasive, transcutaneous approach to assess bone in subjects with OI. 44 However, that study did not investigate specific bone water parameters, or a relationship to mechanical properties. Thus, here we aimed to explore changes in water and other optical spectroscopy-determined parameters and their potential impact on bone mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, assessing deeper into the tissue may provide a more complete view of its bulk composition compared to surface analysis. Further yet, considering that NIR light is non-ionizing, NIR spectroscopy may be applied for the analysis of living tissues and organisms, including in humans [51][52][53][54][55][56]. Considerable advances have been made in these applications in the last few years, including in functional NIR imaging [57,58], and tissue imaging [42,46,49,59,60], which shows the potential to provide valuable data on compositional properties associated with tissue quality and health in situ and in vivo.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…Each hyperspectral image can be comprised of arrays of hundreds to thousands of spectra and allow the analysis of multiple individual components based on the selection of specific intensities or absorbances present in the spectra, presenting an excellent source of information on the amount and distribution of tissue components. Coupled to a fiber optic probe [45,[51][52][53][54][55][56][81][82][83][84][85][86][87][88][89][90][91][92], vibrational spectroscopy allows data to be obtained from intact tissues, and living tissues and organisms, in a nondestructive manner, including from human subjects in clinical settings. This represents an important step forward with the potential to translate this method into an advanced diagnostic tool for monitoring tissue development, quality, disease progression and the effect of therapeutics.…”
Section: Advanced Vibrational Spectroscopy Techniquesmentioning
confidence: 99%
See 1 more Smart Citation